Maqāṣid al-Qur'an sebagai Kerangka Etis untuk Mencapai Pilar Pembangunan Sosial dalam Tujuan Pembangunan Berkelanjutan (SDGs) - Ahmad Muchlishon; Nailil Farohah; Faiz Hidayatullah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2026)
The increasing complexity of global social challenges has intensified the search for ethical frameworks capable of supporting the achievement of the Sustainable Development Goals (SDGs). Although numerous studies have examined the relationship between Islam and sustainable development, limited attention has been given to the Maqāṣid al-Qur'an as a comprehensive ethical framework for advancing the social development pillar of the SDGs. This study aims to examine how the higher objectives of the Qur'an provide normative principles for achieving the five goals within the social development pillar of the SDGs. Employing a qualitative library research design, the study analyzes data derived from the Qur'an, Hadith, official SDG documents, statistical reports published by Statistics Indonesia (BPS), and relevant scholarly literature using thematic content analysis. The findings demonstrate that the Maqāṣid al-Qur'an constitutes a holistic ethical framework through three interrelated dimensions. First, social welfare is established as a theological obligation grounded in faith (īmān) and piety (taqwā), transforming poverty alleviation and social justice into religious responsibilities rather than merely development targets. Second, Islamic philanthropic instruments, particularly ZISWAF (zakat, infaq, ṣadaqah, and waqf), function as strategic institutional mechanisms for translating Qur'anic ethical values into sustainable social policies. Third, prophetic leadership provides the ethical governance necessary to ensure justice, accountability, and public welfare in implementing development programs. This study contributes to contemporary discussions on religion and sustainable development by conceptualizing the Maqāṣid al-Qur'an as an ethical framework that complements the global SDG agenda while offering normative guidance for socially just, inclusive, and sustainable development.